The Competence of the Judiciary in Cases of Document Forgery Conducted by a TNI Soldier Before Joining TNI - Arief Fahmi Lubis (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
One interesting case to examine is when a soldier is suspected of committing the crime of document forgery, which is one of the prerequisites for becoming a TNI soldier before the perpetrator officially becomes a TNI soldier. The objective of this research was to demonstrate the importance of considering the tempus delicti (time of the offense) when determining the jurisdiction of the judiciary. This qualitative research employed a descriptive approach to systematically gather data that were systematic, factual, and expedient in line with the condition when this study was conducted. The findings indicated that when a soldier is suspected of committing the crime of document forgery, a requirement for becoming a TNI soldier before their official enlistment, the jurisdiction of the civilian court system applies.